Pengaruh Kebijakan E-Samsat, Tax Compliance Cost, Kualitas Pelayanan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Dinas SAMSAT Kabupaten Pidie - Sutan Febriansyah; Sri Wahyuni (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of e-samsat policies, tax compliance cost, service quality, and tax sanctions on taxpayer compliance at Pidie Samsat Service. The population in this study is the number of two-wheeled motor vehicle taxpayers whose population is unknown. The population that is not known with certainty is calculated using Lemeshow which produces a sample of 96 respondents. The data analysis methode used multiple linier regression. The results show that tax sanctions have an effect on taxpayer compliance. Meanwhile, e-samsat policies, tax compliance costs an service quality have no effect on taxpayer compliance.